Implementasi Kebijakan Kawasan Tanpa Rokok (KTR) Untuk Mendukung Program Bandara Sehat di Yogyakarta : Implementasi Kebijakan Kawasan Tanpa Rokok (KTR) Untuk Mendukung Program Bandara Sehat di Yogyakarta - Trisnowati, Heni; Nuary Islamiah, Luthfiah; Dzaki Athaya, Hazel; Nine Legoningsih, Astri (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2025)
Yogyakarta International Airport is a new airport that supports public health policies through the implementation of KTR. The KTR policy at YIA Airport is based on Kulon Progo Regent Regulation No.15 of 2020 concerning Amendments to Kulon Progo Regent Regulation No.3 of 2015 concerning Implementation Guidelines for Kulon Progo Regency Regional Regulation No.5 of 2014 concerning KTR. This policy includes a ban on smoking in any place, there is a special room for smoking, free from cigarette advertisements, and there is an appeal for smoking restrictions. The purpose of this study was to determine the implementation of the KTR policy at YIA Airport. This research uses qualitative methods, data collection through interviews involving 6 informants consisting of 5 airport visitors and 1 airport manager, data analysis using QDA miner lite. The results showed that all informants supported the KTR policy on the grounds of health and environmental comfort. This support is shown through approval of rule enforcement, sanctions for violators, and the need for more effective socialization. Some informants suggested educative and preventive approaches to reprimand violators, while others emphasized the importance of the presence of supervisory officers. Regarding facilities, designated smoking areas are considered inadequate both in terms of size and number, as well as the lack of information about their location. Visitor and employee awareness of KTR rules varies, with employees considered more compliant than visitors. The majority of informants support the provision of strict sanctions in the form of fines to increase compliance. Conclusion: the KTR policy at YIA Airport is considered an effective step to create a smoke-free environment, but its success requires the support of socialization, adequate infrastructure, and consistent law enforcement. The implication of these findings is as baseline data to support the realization of a healthy airport in Yogyakarta.